Thymus and activation-regulated chemokine (CCL17) as a clinical biomarker in atopic dermatitis: significance and limitations in the new treatment era - Yoko Kataoka (Frontiers in Allergy)
Thymus and activation-regulated chemokine (TARC; CCL17) is a T-helper-2 chemokine that reflects atopic dermatitis (AD) disease activity. Since 2008, serum TARC levels have been commercially measured in Japan, and clinical experience has shown the usefulness of TARC. The fallacy that eczema is always visible often hinders successful treatment, when there is subclinical inflammation which is inferable from the TARC level. AD treatment has entered a new era with higher therapeutic efficacy. TARC has a different meaning than it did previously, and its significance and limitations are discussed. First, a more appropriate topical therapy monitoring TARC would be useful in selecting truly necessitated patients for expensive new therapies. Dupilumab quickly lowers serum TARC before clinical improvement, and its normalization is not a criterion for dose reduction. However, in some severe cases, TARC may help determine whether to continue treatment. During treatment with JAK inhibitors, serum TARC levels are often elevated and may be abnormally high, leading to the exacerbation of dermatitis. Prurigo nodularis is divided into two types associated with elevated and normal TARC levels, which may aid in the selection of therapeutic agents. In this new era, TARC remains a useful biomarker for more accurate drug selection and the determination of therapeutic efficacy; Currently, in clinical trials of AD, all outcome measurements depend on the clinical score; however the use of a biomarker, such as TARC, as a secondary outcome measure will clarify the characteristics of each drug and the pathophysiological conditions for which it is expected to be effective.